Evidence that adenosine triphosphate or a related nucleotide is the transmitter substance released by non-adrenergic inhibitory nerves in the gut - Burnstock, G. (1970)
1. Stimulation of the vagal non-adrenergic inhibitory innervation caused the release of adenosine and inosine into vascular perfusates from the stomachs of guinea-pigs and toads. 2. Stimulation of portions of Auerbach's plexus isolated from turkey gizzard caused the release of adenosine triphosphate (ATP), adenosine diphosphate (ADP) and adenosine monophosphate (AMP). 3. ATP, added to solutions perfused through the toad stomach vasculature, was broken down to adenosine, inosine and adenine. 4. Of a series of purine and pyrimidine derivatives tested for inhibitory activity on the guinea-pig isolated taenia coli, ATP and ADP were the most potent. 5. ATP caused inhibition of twelve other gut preparations previously shown to contain non-adrenergic inhibitory nerves. The inhibitory action of ATP was not prevented by tetrodotoxin. 6. Quinidine antagonized relaxations of the guinea-pig taenia coli caused by catecholamines or adrenergic nerve stimulation. Higher concentrations of quinidine antagonized relaxations caused by ATP or non-adrenergic inhibitory nerve stimulation. 7. When tachyphylaxis to ATP had been produced in the rabbit ileum, there was a consistent depression of the responses to non-adrenergic inhibitory nerve stimulation but not of responses to adrenergic nerve stimulation. 8. It is suggested that ATP or a related nucleotide is the transmitter substance released by the non-adrenergic inhibitory innervation of the gut.